Średniowieczne pracownie szklarskie w Międzyrzeczu - Sawicka, Joanna (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2015)
Many years of excavation works in the gord in Międzyrzecz have resulted in discovering the remains of three small glass workshops from the second half of the 10th century, the second half of the 11th century and the 13th century. The scarce and typically scattered sources have made it possible to identify the workshops’ nature and, to a very limited extent, the products manufactured there. The discovery included pieces of large and small crucibles, waste from the preliminary stage of glass melting. Most probably, low-alkaline potassium glass was produced there